Art and Politics under Modern Dictatorships : A Comparison of Chile and Romania - Preda , Caterina (Palgrave Macmillan, 2020)
Contents: 1. Art and Politics under Modern Dictatorships: An Introduction2.The Two Modern Dictatorships in Chile and Romania 1970s-19893.Art Should Be Apolitical: Official Art in Chile4.Art Must Be Politicized: Official Art in Romania5.Alternative Art in Chile: Politicized Art6. Alternative Art in Romania: Aesthetic Resistance7.A Model of Comparative Analysis of Art and Politics in Dictatorships.